Principles of English Commercial Law - Burrows, Andrew (Oxford University Press, Incorporated, 2016)
Students will find this book an invaluable overview of the guiding principles of English commercial law. Written by a leading team of experts, it covers the main topics of Agency, Sale of Goods, Carriage of Goods by Sea and by Air and Land, Insurance, Banking, Bailment, Security, and Insolvency.